Outcomes after thoracic endovascular aortic repair (TEVAR) in patients with traumatic thoracic aortic injuries (TTAI) - a single center retrospective review - Chinyepi, Nkhabe (Division of General Surgery, 2019)
Background: Blunt and penetrating traumatic thoracic aortic injuries constitute surgical emergencies that are attended with high mortality rates. Most patients do not survive long enough, post injury, to reach a hospital. On-site mortality rates may approach approximately 85%. Two main treatment options for blunt thoracic aortic injuries (BTAI) are open surgery and thoracic endovascular repair (TEVAR). Penetrating thoracic aortic injuries (PTAI) have a higher mortality than blunt trauma, with patients often only reaching the hospital in extremis. Most will require early intervention. Currently TEVAR is rapidly evolving as the standard of care for thoracic aortic injuries (TAI) at many centres, primarily due to the emerging evidence of lower mortality and morbidity trends in comparison to open surgery (1–4). Methods: From December 2006 to December 2016, 34 patients (30 blunt trauma, 4 penetrating trauma) with traumatic aortic injuries (grades I-IV) were treated with thoracic aortic stent-grafts in the Groote Schuur Hospital Vascular Unit, Cape Town. We assessed the technical and clinical outcomes following TEVAR in these patients. Results: The 30- day mortality rate was 5.8%, corresponding to 2 deaths both associated with the index trauma-related fatal strokes. The overall mortality rate was 11.8% (4/34): three deaths were due to major strokes and one death was related to pulmonary complications. Conclusion: TEVAR after TAI is associated with significantly lower procedural and postoperative mortality. The 30 day and overall mortality after TEVAR in our unit is comparable to international standards. Even though there is a paucity of literature on PTAI, TEVAR has low peri-procedural adverse events and is safe in selected patients.